Infective Costochondritis after Augmentation Mammoplasty: A Rare Case Report and Review of the Literature - Sally Min; Jinil Choi; Kwon Joong Na; Ki Yong Hong (Archives of Plastic Surgery, 2023)
Silicone breast implant insertion is a commonly performed surgical procedure for breast augmentation or reconstruction. Among various postoperative complications, infection is one of the main causes of patient readmission and may ultimately require explantation. We report a case of infective costochondritis after augmentation mammoplasty, which has rarely been reported and is therefore difficult to diagnose. A 36-year-old female visited the clinic for persistent redness, pain, and purulent discharge around the left anteromedial chest, even after breast implant explantation. Magnetic resonance imaging showed abscess formation encircling the left fourth rib and intracartilaginous and bone marrow signal alteration at the left body of the sternum and left fourth rib. En bloc resection of partial rib and adjacent sternum were done and biopsy results confirmed infective costochondritis. Ten months postoperatively, the patient underwent chest wall reconstruction with an artificial bone graft and acellular dermal matrix. As shown in this case, early and aggressive surgical debridement of the infected costal cartilage and sternum should be performed for infective costochondritis. Furthermore, delayed chest wall reconstruction could significantly contribute to the quality of life.